Virtual Selling : A quick-start guide to leveraging video, technology, and virtual communication channels to engage remote buyers and close deals fast - Blount, Jeb (Hoboken, New Jersey : John Wiley & Sons, Inc., 2020)
"A global pandemic. Panic. Social distancing. Working from home. In a heartbeat, we went from happy hours to virtual happy hours. From conferences to virtual conferences. From selling to virtual selling. To remain competitive, sales and business professionals were required to shift the way they engaged prospects and customers. Overnight, virtual selling became the new normal. Now, it is here to stay. Virtual selling can be challenging. It's more difficult to make human to human connections. It's natural to feel intimidated by technology and digital tools. Few of us haven't felt the wave of insecurity the instant a video camera is pointed in our direction. Yet, virtual selling is powerful because it allows you to engage more prospects and customers, in less time, at a lower cost, while reducing the sales cycle. Virtual Selling is the definitive guide to leveraging video-based technology and virtual communication channels to engage prospects, advance pipeline opportunities, and seal the deal. You'll learn a complete system for blending video, phone, text, live chat, social media, and direct messaging into your sales process to increase productivity and reduce sales cycles"--
Includes bibliographical references and index.
"EBSCO evaluates our products based on the Web Content Accessibility Guidelines (WCAG) and the related Section 508 and EN 301 549 regulations in the US and EU. Most EBSCO products are substantially conformant with WCAG 2.2 level AA." Source: https://connect.ebsco.com/s/article/EBSCO-VPATs?language=en_US. Last accessed April 22, 2025.
Description based on online resource; title from digital title page (viewed on July 30, 2020).
Master record variable field(s) change: 650
Keywords: Selling; Sales management -- Automation; Selling -- Information storage and retrieval systems; Electronic books; Electronic books